VOICING TECHNOLOGICAL OBJECTS ON TWITTER: FROM @big_ben_clock to @SelfAwareROOMBA - Johnson, Amy (AoIR Selected Papers of Internet Research, 2014)
On Twitter, existence is envoiced rather than embodied. Twitter is, moreover, broadly egalitarian in its practices of use—any possessor of a valid email address can register for an account. Voices can be directly articulated by a human, a team of humans, a bot, a combination of bot and human. What does it mean that these different voices, bot and human, individual and organizational, performed and animated, interact together as (basically) equals? I examine a collection of Twitter accounts that voice technological objects ranging from clocks to drones to washing machines to ask: Who are we on Twitter?